Student evaluation of teaching enhances faculty professional development - McDonald, Betty (Revue internationale des technologies en pédagogie universitaire / International Journal of Technologies in Higher Education, 2013)
This paper highlights the role of Web 2.0 technologies in sourcing ongoing information from university students in an effort to assist faculty in their continuous professional development (PD), with the ultimate goal of incrementally improving teaching and learning. On a semester basis, students use an online program called CoursEvals to provide their opinions about the course and its instructor. The collected data are used to inform the content and delivery of faculty PD workshops. The interactive nature of CoursEvals, with Web features that facilitate information sharing and interoperatibility with Blackboard, a learning/course management system, make it ideal for impacting higher education. Students can complete student evaluation of teaching (SEOT) online from any location (university, home, mobile, or overseas). This paper underscores the interactive nature of the feedback process that allows faculty, administration, policy makers, and other stakeholders to participate in the ongoing improvement of teaching and learning. We see how Web 2.0 technologies can impact the teaching/learning nexus in higher education, how online forums and Blackboard bulletin boards have helped popularize Web 2.0 technologies, how online social interactions have escalated through wikis, blogs, emails, instant messaging, and audio and video clips, and how faculty can retrieve their personal SEOT at any time and use the information to self- or pee-evaluate at their convenience. Faculty can compare their SEOT over time to determine stability and monitor their classroom effectiveness. They can also address reliability and validity issues and use the information judiciously without making unnecessary generalizations. Researchers will find useful information supporting the impact of Web 2.0 technologies in higher education.